Identification of small Hfq-binding RNAs in Listeria monocytogenes - Christiansen, Janne K. (Cold Spring Harbor Laboratory Press, 2006)

(untitled)
The RNA-binding protein Hfq plays important roles in bacterial physiology and is required for the activity of many small regulatory RNAs in prokaryotes. We have previously shown that Hfq contributes to stress tolerance and virulence in the Gram-positive human pathogen Listeria monocytogenes. In the present study, we performed coimmunoprecipitations followed by enzymatic RNA sequencing to identify Hfq-binding RNA molecules in L. monocytogenes. The approach resulted in the discovery of three small RNAs (sRNAs). The sRNAs are conserved between Listeria species, but were not identified in other bacterial species. The initial characterization revealed a number of unique features displayed by each individual sRNA. The first sRNA is encoded from within an annotated gene in the L. monocytogenes EGD-e genome. Analogous to most regulatory sRNAs in Escherichia coli, the stability of this sRNA is highly dependent on the presence of Hfq. The second sRNA appears to be produced by a transcription attenuation mechanism, and the third sRNA is present in five copies at two different locations within the L. monocytogenes EGD-e genome. The cellular levels of the sRNAs are growth phase dependent and vary in response to growth medium. All three sRNAs are expressed when L. monocytogenes multiplies within mammalian cells. This study represents the first attempt to identify sRNAs in L. monocytogenes.